Moral Lessons of XX-th Century's Genocides - M. L. Polishchuk (Vestnik MGIMO-Universiteta)
In Polishchuk, M.L., Ph.D., professor of decades taught philosophy at MGIMO (University), led Philosophical Club. He is currently a Visiting Professor at several universities in the world the U.S., Israel, Western Europe, continued regular cooperation with (University). This publication is the author of the presentation on russian of his book "The Great inquiry. The philosophy of the balance of history." ( Moscow, the Canon Plus, 2012.)